2013
DOI: 10.1007/s00535-013-0883-1
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity Lens culinaris agglutinin-reactive alpha-fetoprotein assay predicts early detection of hepatocellular carcinoma

Abstract: BackgroundPrognosis of patients with hepatocellular carcinoma (HCC) remains poor because HCC is frequently diagnosed late. Therefore, regular surveillance has been recommended to detect HCC at the early stage when curative treatments can be applied. HCC biomarkers, including Lens culinaris agglutinin-reactive fraction of alpha-fetoprotein (AFP-L3), are widely used for surveillance in Japan. A newly developed immunoassay system measures AFP-L3 % with high sensitivity. This retrospective study aimed to evaluate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(49 citation statements)
references
References 32 publications
1
46
0
Order By: Relevance
“…Numerous studies have investigated the performance of alternative markers or combinations of already established markers. New candidate markers include squamous cell carcinoma antigen-immunoglobulin M complex (SCCA-IGM), α-l-fucosidase [29] , glypican-3 (GPC-3), insulin-like growth factor (IGF) [30] , vascular endothelial growth factor (VEGF), or Dickkopf-1 (DKK1) [31] . Three further biomarkers have intensively been studied for their potential use in screening for HCC, namely Golgi protein 73 (GP73), interleukin-6 (IL-6) and squamous cell carcinoma antigen (SCCA) and were addressed in a recent meta-analysis [32] .…”
Section: Role Of Biomarkers In Surveillance and Diagnosismentioning
confidence: 99%
“…Numerous studies have investigated the performance of alternative markers or combinations of already established markers. New candidate markers include squamous cell carcinoma antigen-immunoglobulin M complex (SCCA-IGM), α-l-fucosidase [29] , glypican-3 (GPC-3), insulin-like growth factor (IGF) [30] , vascular endothelial growth factor (VEGF), or Dickkopf-1 (DKK1) [31] . Three further biomarkers have intensively been studied for their potential use in screening for HCC, namely Golgi protein 73 (GP73), interleukin-6 (IL-6) and squamous cell carcinoma antigen (SCCA) and were addressed in a recent meta-analysis [32] .…”
Section: Role Of Biomarkers In Surveillance and Diagnosismentioning
confidence: 99%
“…In addition, AFP‐L3‐positive HCC showed poor prognosis compared with AFP‐L3‐negative HCC. μTASWako i30 is a diagnostic system that can rapidly measure AFP‐L3 even at very low levels . Quantification of fucosylated AFP levels, but not that of the ratio of AFP‐L3/total AFP, gives some changes in the significance of AFP‐L3 as an early HCC biomarker .…”
Section: Glyco‐biomarkers For Liver Diseasesmentioning
confidence: 99%
“…To address this problem, combined application of DCP- and AFP-based biomarkers has been tested. A novel predictive model comprising AFP-L3, AFP and DCP achieved a sensitivity of 60.6% and specificity of 100% when applied to a cohort of 104 HCC patients, 43% of whom showed AFP levels below 10 ng/mL 27. Meanwhile, a large multicenter case-control study conducted in 201028 suggested that DCP-based diagnostic method coupled with AFP immunoassay for HCC detection resulted in an increase in sensitivity from 65% to 87% at the expense of the specificity score, which dropped from 84% to 69%.…”
Section: Review-biomarkers In Hccsmentioning
confidence: 99%